Maternal breast feeding as a factor of protection for the breast cancer - Clícia Valim Côrtes Gradim; Maria Cláudia Magalhães; Marília de Cássia Ferreira Faria; Cássia Irene Spinelli Arantes (Rev Rene)
This is a quantitative, transversal study which aimed to verify whether women who breastfed relate this act as a protective factor from breast cancer. A form was applied to 200 women who breastfed and attended a municipal clinic in Alfenas-MG, from May to July 2008. Data analysis was based on descriptive statistics and chi-square test, with significance level of 5%. The association index between breastfeeding and breast cancer was 38%. Education level was significantly associated with the knowledge of non-exclusive breastfeeding as a protective factor from breast cancer (p<0.001). Health professionals must encourage women and raise awareness of the advantages of breastfeeding with its benefits for both the child and the mother as a protection against breast cancer.